Competencies and strategies of Al-Qur'an Hadith teachers in developing student potential through LPTQ extracurricular - Aji Ibrahim Lubis, Abdul; Mahariah (UIN Salatiga, 2024)
This study aims to analyze the process of fostering student potential through LPTQ extracurricular activities. The focus of the study in this research on three things, namely the process of fostering student potential through LPTQ extracurricular activities, the competence of the Al-Qur'an Hadith teacher in fostering student potential through LPTQ extracurricular activities and management strategies. The research method used is qualitative based on case studies with data collection techniques through observation, interviews, and documentation studies. The data collected was then analyzed using the Miles and Huberman technique, namely data reduction, data presentation, and conclusion drawing. The research findings explain that there are several forms of student coaching processes through LPTQ extracurricular activities, namely the tahfidz Qur'an program, syarhil Qur'an, fahmil Qur'an, tilawatil Qur'an, and khat Al-Qur'an. The teacher competence in fostering this LPTQ extracurricular program is personality and pedagogical competence. For the management strategy, there are five strategies used, namely choosing the right time, learning methods, grouping students according to their talents, monitoring, and instilling Islamic values.